2017
DOI: 10.1016/j.brainresbull.2016.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of GABAergic synapse development by postsynaptic membrane proteins

Abstract: In the adult mammalian brain, GABAergic neurotransmission provides the majority of synaptic inhibition that balances glutamatergic excitatory drive and thereby controls neuronal output. It is generally accepted that synaptogenesis is initiated through highly specific protein-protein interactions mediated by membrane proteins expressed in developing presynaptic terminals and postsynaptic membranes. Accumulating studies have uncovered a number of membrane proteins that regulate different aspects of GABAergic syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 172 publications
(322 reference statements)
2
30
0
Order By: Relevance
“…Many transmembrane synaptic CAMs, such as NLs, LRRTMs, neurexins, Slitrks, PTPs, and cadherins, typically use characteristic extracellular domains to mediate trans-synaptic interactions to organize and regulate synapse development and function (de Wit and Ghosh, 2016; Lu et al, 2016; Missler et al, 2012). We now report that at hippocampal GABAergic synapses, two major postsynaptic CAMs, NL2 and ST3, interact with each other in cis to control GABAergic synapse development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many transmembrane synaptic CAMs, such as NLs, LRRTMs, neurexins, Slitrks, PTPs, and cadherins, typically use characteristic extracellular domains to mediate trans-synaptic interactions to organize and regulate synapse development and function (de Wit and Ghosh, 2016; Lu et al, 2016; Missler et al, 2012). We now report that at hippocampal GABAergic synapses, two major postsynaptic CAMs, NL2 and ST3, interact with each other in cis to control GABAergic synapse development.…”
Section: Discussionmentioning
confidence: 99%
“…Among these molecules, synaptic cell adhesion molecules (CAMs) are a class of membrane proteins essential for the establishment and maturation of synaptic connections. Recent studies have identified a growing number of synaptic CAMs, including: 1) Neuroligins (NLs) and leucine-rich repeat transmembrane proteins (LRRTMs) that bind to presynaptic neurexins; 2) Slit and NTRK-like family proteins (Slitrks) that bind to presynaptic protein tyrosine phosphatases (PTPs); 3) immunoglobulin superfamily proteins (IgSFs) that mediate trans-synaptic homophilic or heterophilic adhesion interactions; 4) cadherin family proteins; and 5) transmembrane tyrosine kinase receptors (Craig and Kang, 2007; Dalva et al, 2007; de Wit and Ghosh, 2016; Huang and Scheiffele, 2008; Krueger-Burg et al, 2017; Lu et al, 2016; Missler et al, 2012; Sudhof, 2008). While these molecules are involved in various stages of synapse development, how diverse synaptic CAMs work in concert to control synapse formation remains largely unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations suggest that development of GABAergic synapses involves mechanisms distinct from that of glutamatergic synapses. Nevertheless, convincing evidence has demonstrated that cell adhesion molecules are critical for both excitatory and inhibitory synapse development, suggesting that trans-synaptic interactions are a common requirement for the formation of different types of synapses [4, 6, 10, 12]. Interestingly, distinct sets of cell adhesion molecules are enriched at excitatory vs inhibitory synapses [4, 6, 10, 12], suggesting different synaptogenic machineries present at these synapses to instruct their formation respectively.…”
mentioning
confidence: 99%
“…For inhibitory synapses development, Lu et al, [10] discuss the key role of postsynaptic transmembrane molecules in the development of GABAergic inhibitory synapses, including NMDA receptors, GABA A receptors, synaptogenic cell adhesion molecules and immunoglobulin superfamily proteins. Wierenga [20] highlights the importance of local exchange of synaptic adhesion molecules, actin dynamics and activity-driven fine-tuning in GABAergic presynaptic development.…”
mentioning
confidence: 99%